Immunocytochemical Methods and Protocols - Javois, Lorette C;Ed (Methods in Molecular Biology (Clifton, N.J.), v. 115., 1999)
In Animal Cell Biotechnology, scientists with long-refined expertise describe cutting-edge techniques for the production of therapeutic proteins and vaccines. Capturing the major advances that have occurred in both the science and the technology of these biopharmaceuticals, this important book covers the powerful new techniques used in genetically manipulating animal cells, optimizing their growth in defined media (particularly at large- scale), avoiding contamination, and in the harvesting and analysis of cell products. Topics include basic culture facilities and methods; molecular methods for gene transfection; cell immortalization and cell fusion; and techniques for the study of cell growth, viability, metabolism, and productivity. Animal Cell Biotechnology constitutes a comprehensive manual of state-of-the-art techniques for setting up a cell culture laboratory, maintaining cell lines, and optimizing critical parameters for cell culture. This authoritative book will significantly aid researchers in developing new monoclonal antibodies, vaccines, anticancer agents, and drugs for the widest spectrum of cardiovascular, respiratory, and immune diseases.